2018
DOI: 10.1021/acs.est.7b05389
|View full text |Cite|
|
Sign up to set email alerts
|

Amendment of Agricultural Soil with Metal Nanoparticles: Effects on Soil Enzyme Activity and Microbial Community Composition

Abstract: Several types of engineered nanoparticles (ENPs) are being considered for direct application to soils to reduce the application and degradation of pesticides, provide micronutrients, control pathogens, and increase crop yields. This study examined the effects of different metal ENPs and their dissolved ions on the microbial community composition and enzyme activity of agricultural soil amended with biosolids. The activity of five extracellular nutrient-cycling enzymes was measured in biosolid-amended soils tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(89 citation statements)
references
References 58 publications
3
84
1
1
Order By: Relevance
“…Perturbations in microbial community structure due to these nanoparticles have also been reported in other soils [86][87][88]. These studies have used a wide range of concentrations of silver nanoparticles from 0.01 µg/g to 1815 µg/g of soil and varying exposure times, of one day to one year [39,72,[82][83][84][85]89]. Two of these studies have also described bacterial communities recovering after 21 to 50 days following an initial shift [35,84].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Perturbations in microbial community structure due to these nanoparticles have also been reported in other soils [86][87][88]. These studies have used a wide range of concentrations of silver nanoparticles from 0.01 µg/g to 1815 µg/g of soil and varying exposure times, of one day to one year [39,72,[82][83][84][85]89]. Two of these studies have also described bacterial communities recovering after 21 to 50 days following an initial shift [35,84].…”
Section: Discussionmentioning
confidence: 87%
“…The preliminary nature of the work does not permit definite conclusions to be drawn with respect to diversity. However, changes in soil bacterial diversity have been described in earlier studies in the presence of silver nanoparticles [38,[82][83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the spatial structure imposed by soil particles resulting in local variations in oxygen availability over small distance [81], both aerobic and anaerobic conditions can be found in the same soil sample. Thus, AgNO 3 control could act as substrate for nitrate reducing bacteria, such as gamma-Proteobacteria or Acidobacteria [63,82,83], which were less sensitive to AgNP or Ag + in form of AgNO 3 [78,84,85] and promoted their increase due to nitrate utilization via denitrification and/or dissimilatory nitrate reduction [81,83] resulting in new nitrogen sources for the ammonia-oxidizing and nitrogen fixing bacteria.…”
Section: Table 4 Pairwise Comparisons (P) Of the Post-hoc Test N = 2400mentioning
confidence: 99%
“…The composition of bacterial communities in restored soil differed significantly ( P < .05) from those in native soil and changed with restoration time. A decrease in the abundance of soil microorganisms also occurred in response to other disturbances, including chloroform fumigation, fire, pesticides, heavy metal ions, or engineered nanoparticles in the soils …”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the abundance of soil microorganisms also occurred in response to other disturbances, including chloroform fumigation, 18 fire, 24 pesticides, 23 heavy metal ions, 25,26 or engineered nanoparticles in the soils. 27,28 Griffiths et al reported random changes in the dominant bacteria that occurred after the chloroform fumigation. 18 In this study, all microorganisms were reduced or eliminated from the autoclaving, as indicated by no detectable MBC or extractable trace DNA in the autoclaved soil.…”
Section: Bacteria Resilience In Disturbed Soilmentioning
confidence: 99%